2017
DOI: 10.1016/j.bbagen.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of major isoquinoline alkaloids from Chelidonium majus towards telomeric G-quadruplex: A study using a transition-FRET (t-FRET) assay

Abstract: BackgroundNatural bioproducts are invaluable resources in drug discovery. Isoquinoline alkaloids of Chelidonium majus constitute a structurally diverse family of natural products that are of great interest, one of them being their selectivity for human telomeric G-quadruplex structure and telomerase inhibition. MethodsThe study focuses on the mechanism of telomerase inhibition by stabilization of telomeric Gquadruplex structures by berberine, chelerythrine, chelidonine, sanguinarine and papaverine. Telomerase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 59 publications
0
28
0
Order By: Relevance
“…[13] Berberine (Figure S2) and its derivatives have been shown to stabilize telomeric G4s and inhibit telomerase. [14] We recently found that EPI (Figure 1c) exhibits great fluorescence enhancement upon binding to human telomeric G4 in K + solution, up to 45 times stronger than other G4s and double-stranded and single-stranded DNA. [15] Here, we report that EPI specifically recognizes the hybrid-2 telomeric G4 and we elucidate the molecular mechanism for this specific recognition by NMR structure determination of the 1:1 EPI-wtTel26 complex in K + solution.…”
mentioning
confidence: 99%
“…[13] Berberine (Figure S2) and its derivatives have been shown to stabilize telomeric G4s and inhibit telomerase. [14] We recently found that EPI (Figure 1c) exhibits great fluorescence enhancement upon binding to human telomeric G4 in K + solution, up to 45 times stronger than other G4s and double-stranded and single-stranded DNA. [15] Here, we report that EPI specifically recognizes the hybrid-2 telomeric G4 and we elucidate the molecular mechanism for this specific recognition by NMR structure determination of the 1:1 EPI-wtTel26 complex in K + solution.…”
mentioning
confidence: 99%
“…Relative average telomere length can be measured by MMQPCR using primers that hybridize with the telomere hexamer repeats because the number of binding sites for the primers increases as average telomere length increases [ 37 , 38 ]. However, MMQPCR simultaneously counts the copy number of albumin as a single copy gene in each reaction tube using a specific primer pair, so the relative amount of telomere copies (T) to albumin (S) of the untreated control is measured.…”
Section: Resultsmentioning
confidence: 99%
“…Natural bioproducts are invaluable resources in drug discovery [28]. Many reports have documented the antitumor effects of essential oils and their bioactive compounds.…”
Section: Discussionmentioning
confidence: 99%